2021
DOI: 10.1002/ange.202114577
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Dithia[5]helicenes and their Postsynthetic Functionalization to Access Dithia[9]helicenes

Abstract: A highly enantioselective synthesis of 5,13-disubstituted dibenzo[d,d']benzo [1,2-b:4,3-b']dithiophenes is reported. Key for the successful assembly of these helical architectures is the last two successive Au-catalyzed intramolecular alkyne hydroarylation events. Specifically, the second cyclization is the enantiodetermining step of the whole process and provides the desired helicenes with excellent ee values when a TADDOL-derived 1,2,3-(triazolium)phosphonite moiety (TADDOL: α,α,α', is employed as an ancilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The applicability of ligand L20B was further extended with the report by the Cauteruccio and Alcarazo group, 124 wherein the gold(I) complex of the ligand was found efficient for a double intramolecular hydroarylation of tailored diynes (20f ) to produce dithia[5]helicenes (20g) with an enantiomeric excess of up to 98% (Scheme 20C). Notably, the post-synthetic functionalization allows π-extension of the framework without much loss of ee.…”
Section: α-Cationic Phosphonite Ligandsmentioning
confidence: 94%
“…The applicability of ligand L20B was further extended with the report by the Cauteruccio and Alcarazo group, 124 wherein the gold(I) complex of the ligand was found efficient for a double intramolecular hydroarylation of tailored diynes (20f ) to produce dithia[5]helicenes (20g) with an enantiomeric excess of up to 98% (Scheme 20C). Notably, the post-synthetic functionalization allows π-extension of the framework without much loss of ee.…”
Section: α-Cationic Phosphonite Ligandsmentioning
confidence: 94%
“…[62][63][64][65] Recently, this method was expanded by Cauteruccio and Alcarazo and applied to thiophene-based structures, and a series of dithia [5] helicene derivatives 54 were produced through highly enantioselective gold-catalyzed alkyne hydroarylation of alkyne precursors 53 (Scheme 12). 66 The enantioselectivity of the transformation from 53 to 54 arises from the use of a specific chiral gold complex catalyst, which has previously been shown to induce excellent selectivity in the hydroarylation of alkynes. 63 HPLC analysis showed that the enantioselectivity of the first trial was excellent (92% ee), and a very wide scope of 20 alkyne derivatives of 53, possessing different substituents, were screened, resulting in varying moderate-to-excellent yields (53-98%) and varying enantioselective success (33-98% ee).…”
Section: π-Extended Heterohelicenesmentioning
confidence: 99%